An indoor positioning system based on distributed LTE network - Yu YANG; Ming CHEN; Daqing LIU (Dianxin kexue)
Indoor positioning technology has important applications in the business and security fields,but there are still existing problems with low positioning accuracy and high deployment costs.An indoor positioning system based on long term evolution ( LTE ) network was introduced.The system was defined on the Huawei distributed pico base station and was used to measure the reference signal strength (RSRP) or time of arrival (ToA) of mobile terminals to multiple access points.To overcome the uplink power control in LTE network,the absolute RSRP or ToA was converted to differential values.The system relied on widely deployed LTE networks to provide seamless location services to terminal devices in a wireless network connection state.It didn’t rely on third-party software or affect network performance.The experimental results show that the average positioning accuracy of Huawei indoor positioning system using time difference of arrival (TDoA) can reach 3~5 m in indoor scenarios such as shopping malls,showing good application potential.